2008
DOI: 10.1021/pr800392s
|View full text |Cite
|
Sign up to set email alerts
|

Protein Expression Profile of the Mouse Metaphase-II Oocyte

Abstract: The mature oocyte contains the full complement of maternal proteins required for fertilization, the transition to zygotic transcription, and the beginning stages of embryogenesis. Many of these proteins have yet to be characterized. In this study, two-dimensional electrophoresis (2-DE) of mouse metaphase-II (MII) oocyte proteins, stained with silver staining or Pro-Q Diamond dye, was performed to describe the proteome and phosphoproteome of the mouse oocyte derived from ICR mice. A total of 869 selected protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
3
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 71 publications
3
60
3
2
Order By: Relevance
“…During the past decades, several approaches analyzing the protein composition of oocytes have been conducted to obtain the proteome signatures of Xenopus, bovine, pig, and mouse oocytes (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Calvert et al (15) identified eight highly abundant heat shock proteins and related chaperones in the mature mouse egg by two-dimensional difference gel electrophoresis (DIGE).…”
mentioning
confidence: 99%
“…During the past decades, several approaches analyzing the protein composition of oocytes have been conducted to obtain the proteome signatures of Xenopus, bovine, pig, and mouse oocytes (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Calvert et al (15) identified eight highly abundant heat shock proteins and related chaperones in the mature mouse egg by two-dimensional difference gel electrophoresis (DIGE).…”
mentioning
confidence: 99%
“…It was also reported that some of the placental abnormality of nuclear transfer embryos can be blamed on the abnormal expression of some genes, such as HSPC117 . Furthermore, protein profile of the mouse metaphase-II oocyte was analyzed, which might be valuable in revealing potential mechanisms of epigenetic reprogramming in nuclear transfer (Ma et al, 2008).…”
Section: Nuclear Transfermentioning
confidence: 99%
“…In a subsequent study by Ma et al, (2008), two-dimensional electrophoresis of mouse metaphase-II (MII) ooplasmic proteins (the ZP was removed by digestion before protein extraction) was performed to describe the proteome and phosphoproteome of oocytes derived from ICR mice. A total of 869 selected protein spots, corresponding to 380 unique proteins, were identified successfully by mass spectrometry.…”
Section: Proteomic Studies In the Mouse Oocytementioning
confidence: 99%
“…Studies in farm animals, such as cattle and pigs, have been performed for both qualitative database generation and for quantification of proteome changes during oocyte IVM (bovine: Coenen et al, 2004;Bhojwani et al, 2006;Massicotte et al, 2006;Memili et al, 2007;Berendt et al, 2009;pig: Ellederova et al, 2004;Susor et al, 2007, reviewed by Ma et al, 2008;Arnold & Frohlich, 2011). Berendt et al (2009) performed two-dimensional gel electrophoresis saturation labeling to detect quantitative differences in the proteomes of immature versus IVM-MII bovine oocytes.…”
Section: Proteomic Studies In Farm Animal Oocytesmentioning
confidence: 99%